Identifying Factors that Influence Student Success in Clinical Laboratory Sciences Program. - NASR, PAYMAN; JACKSON-HARRIS, CHERYL (Clinical Laboratory Science)
The profile of today's college students looks quite different than it did decades ago, when the average student was a recent high school graduate moving directly from high school to university. Students today are older, work to support themselves and their families, and are ethnically more diverse than their peers of decades past. The student demographic shifts necessitate regular evaluation of academic programs including reevaluating admissions requirements, financial aids availability, and schedule flexibility to meet the demands of the new student demographics. Clinical Laboratory Sciences (CLS) at California State University Dominguez Hills (CSUDH) is the largest CLS program in Southern California and is accredited by National Accrediting Agency for Clinical Laboratory Sciences (NAACLS). The program admits both undergraduate and post-baccalaureate candidates for training as Clinical Laboratory Scientists for careers in healthcare or research. Despite the great success in graduating well qualified candidates, there has been a trend in which a larger portion of students spend more time than expected to complete the program requirements. This phenomenon prompted the faculty at CSUDH to seek the causes for such lengthening time towards graduation. In the current study, we report the results of survey questionnaire that was submitted to CLS students at CSUDH in 2015. The results confirm the recent shift in student demographics in the CLS program and identify the primary obstacle towards a timely graduation to be inability to register for required courses due to schedule conflicts and/or intense competition for available seats.